The perceived value of management information systems in a South African public institution - Bongekile I. Stuurman; Kagiso Mabe (South African Journal of Information Management, 2025)
Background: Management Information Systems (MISs) act as support units that store, process, and organise information for organisations. However, poorly maintained MISs can adversely affect an organisation’s success or survival due to the inability to make quality decisions. Many public institutions face challenges in implementing MISs, making it essential to investigate the value derived from using MISs and the challenges associated with their implementation and use.